PENGARUH RETURN ON EQUITY (ROE), CURRENT RATIO (CR), DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETURN SAHAM PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tendri Nofta Febrianti; Enggar Diah Puspa Arum; Riski Hernando (Jurnal Akuntansi Kompetif, 2026)
This study aims to determine the effect of Return on Equity, Current Ratio, and Debt to Equity Ratio on stock returns in property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. This research is quantitative. The data used are secondary data in the form of annual reports and company financial statements. The sample selection technique in this study used total sampling. A total of 70 samples were used from 94 companies during the study period. Data analysis was performed using multiple linear regression analysis with the help of SPSS. The results show that simultaneously, Return on Equity, Current Ratio, and Debt to Equity Ratio have a positive and significant effect on stock returns. Meanwhile, partially, Return on Equity has a positive and significant effect on stock returns. Meanwhile, the Current Ratio and Debt to Equity Ratio have no effect on stock returns.